Deriving inputs for environmental conservation in using various N carriers for rice in rice-wheat cropping system - KUMAR, AJEET; KOHLI, ANSHUMAN; DUTTA, SUDARSHAN K.; SINGH, Y.K.; SINGH, MAHENDRA; GHOSH, MAINAK; GUPTA, S.K. (Journal of Soil and Water Conservation, 2023)
The differential release pattern of ammoniacal and nitrate forms of nitrogen through various carriers creates varying availability of nitrogen for the crops in the soil; which often does not synchronize with the crop demand. This presents an opportunity for nitrogen losses to the environment and calls for better synchronization of N supply and crop demand. A study was conducted to know the effect of various N sources on soil nitrogen availability in transplanted rice. The experiment was laid out in a randomized block design with three replications and consisted of ten treatments viz. T1 (100% N though prilled urea (PU)); T2 (100% N through neem coated urea (NCU)); T3 (Basal N through Ammonium sulphate and rest N top dressed with NCU); T4 (Basal N through Calcium Nitrate and rest N top dressed with NCU); T5 (Basal N through Di-ammonium phosphate and rest N top dressed with NCU); T6 (100% N through S- coated prilled urea); T7 (100% N through S-coated neem coated urea); T8 (Control (without N)); T9 (Unfertilized (without NPK)) and T10 (Soil test based fertilizer recommendation). The NE recommended dose of these fertilizers were applied at the time of transplanting of rice (var. Sahbhagi Dhan) as basal dose with top dressing (two times). Results suggest that N availability up to 30 DAT was found to be higher in PU treated plot in comparison other N carriers. However, after 30 days of transplanting, N availability was found to be higher in case of SCNCU, NCU and SCPU in comparison to prilled urea and this trend prevailed till the end of the cropping season. The significantly lower grain yield, AEN and AREN were recorded in PU treated plots in comparison to other N carriers due to rapid hydrolysis of prilled urea that was very susceptible to losses through volatilization. The study confirmed that the NE recommended fertilizer application with SCNCU and NCU can increase NUE and avoid N loss and protect the environment.